2016
DOI: 10.1021/acs.jnatprod.6b00645
|View full text |Cite
|
Sign up to set email alerts
|

Acetophenone Monomers from Acronychia trifoliolata

Abstract: Seven new [acronyculatins I–O (1–7)] and four known acetophenone monomers were isolated from a CH3OH/CH2Cl2 (1:1) extract (N089419) of Acronychia trifoliolata provided by the U.S. National Cancer Institute (NCI, Frederick, MD, USA). Their structures were characterized by using various NMR and HRMS techniques. Among the known compounds, the structure of acronyculatin B (8) was revised. Some of the isolated compounds were evaluated for antiproliferative activity against human cancer cell lines. While most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…The physical data ( 1 H NMR, 13 C NMR, HRMS) were essentially identical to the reported data for the natural product. 9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical data ( 1 H NMR, 13 C NMR, HRMS) were essentially identical to the reported data for the natural product. 9 …”
Section: Methodsmentioning
confidence: 99%
“…7 In the course of the discovery of unknown bioactive natural products from rainforest plants, six new acetophenone monomers, named acronyculatins I ( 1 ), J ( 2 ), K ( 3 ), L ( 4 ), M, N ( 5 ), and O ( 6 ), were isolated from a 1:1 CH 3 OH/CH 2 Cl 2 extract of this plant. 9 In addition, the structure of acronyculatin B ( 7 ), originally identified by Su et al, 10 was revised to be 1-[6-hydroxy-2-(2-hydroxypropan-2-yl)-4-methoxy-7-(3-methylbut-2-en-1-yl)-2,3-dihydrobenzofuran-5-yl]ethan-1-one based on extensive NMR studies. Because the isolation was performed on a limited amount (4.9 g) of extract provided by the U.S. National Cancer Institute (NCI), and no more material was available, small quantities of each compound were obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a continuing investigation on bioactive compounds from rainforest plants, 10 L. corymbulosa was selected for exploration of its cytotoxic components. A CH 3 OH–CH 2 Cl 2 (1:1) extract of the bark of this species (N005829), as provided by the U.S. National Cancer Institute (NCI, Frederick, MD, USA), was found to exhibit broad cytotoxicity in the NCI-60 human tumor cell assay (IC 50 < 10 µg/mL against all 60 cell lines, as performed by NCI in 1989).…”
mentioning
confidence: 99%
“…[13,14] We previously reported the new acetophenones acrophenone A, B and C and several known acetophenone dimer compounds, [15] such as acrovestenol and acrovestone. Previous reports [9,11,[16][17][18] have indicated that the biological activities of acetophenone monomers are low. Our experiments have also shown that the acetophenone monomers prenylacronylin and acronylin, which are predicted to be components in acetophenone dimers, have cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%